Efforts to Improve Students' Disciplinary Character by Implementing Morning Assembly: Action Research at MIS AL-Fatah Siiyang - Nurliah (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to improve students' disciplinary character through the implementation of morning assemblies at MIS AL-Fatah Siiyang. Discipline is a fundamental aspect of character education that significantly influences students' academic and social development. However, observations in the initial stages of this research revealed that many students lacked punctuality, failed to follow school rules consistently, and showed limited engagement in morning routines. Therefore, a classroom action research (CAR) design was employed, consisting of two cycles with stages of planning, action, observation, and reflection. The participants in this study were 25 students in the fifth grade during the 2024/2025 academic year. Data were collected using observation sheets, field notes, interviews, and documentation, and were analyzed qualitatively and quantitatively. The findings indicate that the implementation of morning assemblies significantly improved students’ disciplinary behaviors. In the first cycle, students began to show improvements in punctuality and participation, but inconsistencies were still noted. After adjustments and enhancements in the second cycle including more structured routines, motivational messages, and active student involvement the number of students arriving on time increased from 56% to 88%, while adherence to school rules rose from 62% to 91%. In addition, teachers reported improved student attitudes, such as respect, responsibility, and cooperation. These results suggest that morning assemblies, when implemented consistently and meaningfully, can serve as an effective strategy to foster discipline among elementary school students. In conclusion, this study emphasizes the importance of integrating character education into daily school routines. The morning assembly, as a simple yet impactful practice, offers a strategic platform to shape students’ behavior and instill positive values from an early age. This research contributes to the growing body of literature on character development in Islamic elementary schools and offers practical insights for educators seeking to enhance student discipline through school-wide initiatives.